.IMPLEMENTASI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN ANAK TERHADAP ANAK SEBAGAI TERSANGKA TINDAK PIDANA NARKOTIKA - Sania, Ayu; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Criminal act of narcotics from year to year has increased, both in terms of a suspect and victims of narcotic crimes. Especially for children, because they are an asset of the nation, as part of the young generation of children play a very strategic role as a nation's successor. For that, Indonesia has been keep their assets by creating Law Number 11 Year 2012 about Criminal Justice System of the Child. so the children who?re caught in the law case still be considered. The purpose of this thesis to know the implementation of that law in investigation process children?s case of narcotics to police of peekanbaru city.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in the City Police Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, the data tertiary data collection techniques in this study with 2 methods ie interviews and review of the literature.From the result of research by the author can be concluded. First, investigation for child criminal act are different with the adult. Second, the difference just for process, time periode, and the investigation do by great police. Third, the obstacles that police faced is hard to find the additional evidence, need time for research and there?s no jail for children.Keywords: Criminal act ? Investigation ? Child Criminal Justice System ? Narcotics.